2016
DOI: 10.1063/1.4946883
|View full text |Cite
|
Sign up to set email alerts
|

Table-top two-color soft X-ray laser by means of Ni-like plasmas

Abstract: Laser-produced Ni-like plasmas are known as active media for extreme ultraviolet lasing, with the flexibility to two-color lasing. Two-color laser generation is very complex at accelerator facilities. In this work, plasma lasing at the 3d 9 4d 1 (J ¼ 0) ! 3d 9 4p 1 (J ¼ 1) (collisional-pumping process) and the 3d 9 4f 1 (J ¼ 1) ! 3d 9 4d 1 (J ¼ 1) (photo-pumping process) transitions is studied experimentally and computationally. Several key characteristics of collisional-and photo-pumping laser, such as diverg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
(52 reference statements)
0
10
0
Order By: Relevance
“…In particular, the two-color scheme used to prepare and probe the spectra of radical anions is very interesting. It should be mentioned that Masoudnia et al 105 have shown two-color so X-ray lasing on a tabletop laser setup.…”
Section: Laser Mass Spectrometrymentioning
confidence: 99%
“…In particular, the two-color scheme used to prepare and probe the spectra of radical anions is very interesting. It should be mentioned that Masoudnia et al 105 have shown two-color so X-ray lasing on a tabletop laser setup.…”
Section: Laser Mass Spectrometrymentioning
confidence: 99%
“…0.12 nm (10'332 eV). Masoudnia et al 3 have summarized the three beamline architectures that are functional to generate two-color pulses, i.e. (i) double split undulator mode, (ii) gain-modulated undulator mode, and (iii) double-bunch undulator mode.…”
Section: Introductionmentioning
confidence: 99%
“…Different authors agree that the thick plasma requires radiative pumping at ca. 350eV (3.53nm) 3,7 . Such soft X-ray pump may be calculated as the peak radiation for a black-body emitter at a temperature of 70eV, using Wien's law.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations